Approaching Tokoyo from Cognitive Archaeology - Falero Folgoso, Alfonso (Estudios Complutenses de Asia Oriental, 2025)
In the Japanese imagination, the natural and the supernatural are not opposed to each other, but often complement each other. Moreover, they do not usually occupy ontologically separate spaces. However, there is an exception in the case of the tokoyo 常世or ’eternal world’ in Japan. As its very name reveals, it is a world parallel to our own, but its radical difference lies precisely in the most ontological feature that makes our world mundane: its ephemerality, its transience, its being-in-time. Tokoyo, on the other hand, is a timeless world, not subject to change, a distinctive mark (merkmal) of temporality. In Japan, as in many other cultures, an eternal, unchanging world has been imagined since ancient times. Before the Buddhist imagination arrived and the Japanese dreamed of paradises that rescue the erratic souls of the departed, Japanese literature already refers to this world, and refers to it as an utopia. A faraway place, unreachable by human means, where it is difficult to travel to, but not the return journey. The inhabitants of this world deign to visit ours. In this way they bring their extraordinary virtues as exceptional visitors endowed with great power. A power that is almost always constructive, but which in some cases is perceived as a questioning of local power up there. Imagined beyond the horizon, it is a transoceanic place. In this proposed analysis, we explore the cultural and symbolic referents that contribute in classical Japanese literature to give visible form to an ontological concept that is difficult to imagine. At the same time, we study the interrelation between several imaginaries that come to configure a hybrid idea, nourished in more than one tradition, heterogeneous among themselves. On a more universal level, it is proposed to understand this symbolic concept in relation to the prototype of the "island of the blessed" present in all the cultures of Eurasia.